Development of Pilgrimage Tourism in Samarkand - Rakhimov Zafar Odilovich; Oltinova Makhliyo Sukhrobovna (International Journal on Economics, Finance and Sustainable Development, 2026)
This article examines the development of pilgrimage tourism in Samarkand as an important aspect of Uzbekistan's tourism industry. It analyzes the region's historical and cultural resources, their importance in attracting tourists and pilgrims, and current trends in tourism infrastructure development. Particular attention is paid to the role of religious and historical monuments, such as mausoleums, mosques, and ancient complexes, which shape Samarkand's unique tourism potential. The paper also examines statistical indicators of tourist flow, the impact of tourism development on the region's economy, and prospects for further growth. The study demonstrates that pilgrimage tourism contributes to strengthening the country's international image and fostering intercultural dialogue.